The ‘Third Platform’ and New Education Requirements - Nesterov, Vyacheslav; Mikhailova, Elena (Computer Tools in Education, 2017)
This article discusses some of current trends in the IT higher education. Current development of the computer industry as well as respective new challenges to higher education are analyzed. The article deals with the changes implemented in the IT curricula, as well as education technology changes. The reasons of strengthening links between education and industry are explained.